Fruit Low-Alcoholic Beverages with High Contents of Iridoids and Phenolics from Apple and Cornelian cherry (Cornus mas L.) Fermented with Saccharomyces bayanus - Kinga Adamenko; Joanna Kawa-Rygielska; Alicja Kucharska; Narcyz Piórecki (Polish Journal of Food and Nutrition Sciences)
In this study, we produced novel, natural and fermented apple-Cornelian cherry beverages rich in natural antioxidants. These products were examined for their physicochemical parameters, and antioxidative properties as well as subjected to the quantitative and qualitative identification of iridoids and phenolics. The highest concentration of total phenolics determined with the Folin-Ciocialteu method (964.28 mg GAE/L) and the strongest antioxidative properties measured with the DPPH • , ABTS •+ , and FRAP tests (7.90, 11.04, and 12.86 mmol TE/L) were determined in the beverages with the addition of juice from red-fruit Cornelian cherry. The most numerous group of compounds in the analyzed beverages were iridoids, with loganic acid (LA) found to predominate (424 mg/L). Results obtained demonstrate that the addition of juice from Cornelian cherry fruits during the production of fermented apple beverages causes a significant increase in their antioxidative properties, modifies their phenolics profile, and allows enriching them with iridoids.